Entrapment of central venous catheter by a suture to the left atrial wall following double valve replacement - Gyawali, Bidhan; Amatya, Ashsish Govinda; Shrestha, Battu Kumar; Pokharel, Jeju Nath; Gautam, Nabin Chandra (Journal of Society of Anesthesiologists of Nepal, 2015)
A 19-year-old female with severe mitral stenosis, moderate mitral regurgitation and severe aortic regurgitation was scheduled for double valve replacement. The central venous catheter inserted after induction of anesthesia could not be pulled out on an attempt to remove it on third postoperative day, and appeared to be stuck. Fluoroscopy confirmed the fixation of catheter at left atrial wall of the heart. This necessitated reopening the chest, cutting the suture and removing the catheter. We believe that our case is one of the few reports of central venous catheter sutured surgically to the atrial wall requiring re-exploration for removal. This kind of entrapment of central venous catheter by a suture is a possible complication in open heart surgeries. Cardiovascular anesthesiologists and surgeons should take measures to prevent such complication. Any attempt to pull it out could be fatal. Cautious handling is advocated whenever an entrapped central venous catheter is found. Checking the catheter for possible entrapment by gently pulling it a few centimeters at the time of atrial wall closure and using a shorter length catheter may be the strategies to prevent such complication. Journal of Society of Anesthesiologists 2014 1(2): 80-82